Implementación de un plan de recuperación de cartera en el Gobierno Autonomo Descentralizado municipal de La Maná correspondiente al año 2011 - Rivera Vernaza, Zoila (2012)
The object of the research present was to implement a Losing Wallet Recovery Plan in the Municipal Decentralized Autonomy Government to The Manna canton of the Cotopaxi Province, in the year 2011, for to improvement the liquid indicators and to fortify the finances states of the sectional organism; for effect it is formulate: to diagnose the impact of losing wallet in the finances states of the Municipal Decentralized Autonomy Government to The Manna canton. To proposal and strategies for the losing wallet recovery; to evaluate the benefit of the proposal thorough technical’s and finances indicators. It was identify with a problem principal, which the 30% municipal input was includes in the losing wallet ($59.130 to December of the year 2011), with the classification next: rural property, $11.492,70 in the year 2008 and $18.157,65 in the year 2011, with an increase of the 58% in the three years, urban property and potable water services, by the strategies fault for which the citizenship pay this debt to the municipal institution. For this reason, the opinion poll and interview applied to the personal of the Finances Area, who realize functions of the collection of the urban and rural property, potable water service and others counts, they say which is necessary the elaboration of the procedure manual whit strategies for the losing wallet recovery in the counts of the urban and rural property, potable water service and others, for the fortify of the currents actives o the institution and the liquid recovery of the Municipal Decentralized Autonomy Government to The Manna canton, benefit this Losing Wallet Recovery Plan. The institution and to the citizenship in general, because improvement will the public’s handiwork and services offer by part to the Municipal Decentralized Autonomy Government to The Manna. Key words: Plan, Recovery, Wallet, Losing.